Oral Presentations Abstracts: THE ETHICS OF E-CIGARETTES FOR SMOKING CESSATION: A GLOBAL CHALLENGE - MEGHEA, Cristian I.; BLAGA, Oana; DASCAL, Marina; FRATILA, Teodora; SANDU, Petru; COLOSI, Horatiu (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Tobacco smoking is especially harmful for women because, in addition to its effects on mortality and morbidity, it negatively impacts pregnancy, reproductive, and health of the offspring. Data from our work in Romania revealed that pregnant tobacco smokers are seeking information and clinical advice related to e-cigarette use as a tobacco cessation approach. E-cigarette use increased rapidly in the recent years in the US and in other countries, including LMICs. The tobacco control field is deeply divided on how to respond to the increase in e-cigarette use. Additional evidence on the ethical issues related to e-cigarette use and tobacco cessation will inform our mHealth and other pregnancy tobacco cessation interventions and will guide future tobacco control policy direction. The objective of this study is to identify ethical concerns and associated attitudes and perceptions related to e-cigarette use for tobacco cessation during pregnancy among pregnant smokers, their life partners, medical professionals, and other stakeholders. We will interview (N=20) and conduct two focus groups with women who smoke (one focus group, N=10) and women who quit during pregnancy (one focus group, N=10); interview life partners (N=10) of such women; interview ObGyn physicians (N=10) and nurses (N=10); and interview (N=10) and conduct one focus group (N=10) with perinatal educators. Other relevant stakeholders will be also interviewed including the leadership of 2035 Tobacco Free Romania, the national Stop Smoking program, the Pure Air consortium, the Romanian Pneumology Society, the SAMAS NGO focused on maternal and child health and rights, and others. With respect to expected outcomes, the proposed application is anticipated to advance understanding of the smokers’ and other stakeholders’ ethical concerns and associated attitudes and perceptions related to e-cigarettes use for tobacco smoking cessation. The in-depth new knowledge will have a positive impact on the cessation of prenatal and postnatal tobacco smoking and will inform future tobacco control policy directions. Results will be available and will be presented at the time of the conference.